PETROPHYSICAL ANALYSIS, RESERVOIR CHARACTERIZATION, AND HYDROCARBON RESERVES ESTIMATION IN TAWUN FORMATION, SUKUREJO FIELD, NORTH EAST JAVA BASIN. - Dwi Kurniawan, Bagus
Sukorejo field is one of the oil fields located in Cepu, Blora Regency, North East Java Basin. This field is currently considered as a development field within coverage area approximately 12 km2. The focus of the research on Sukorejo field is Tawun Formation at layer V and layer VIII. The main purposes of this study are to know the geological setting of Sukorejo field, determine reservoir characterization of Tawun formation such as depositional facies, distribution of reservoir properties, and volumetric estimation of Original Oil In Place (OOIP) prospect. The data used in this research consists of core and cutting descripsions, petrographic reports, biostratigraphy reports, 3D seismic, checkshot, and electric log from 30 wells. Several methods have been performed in order to achive those main purposes which are litofacies analysis, electrofacies analysis, biostratigraphy analysis, facies association and environmental deposition , sequence stratigraphy analysis, petrophysical analysis, 3D static reservoir modelling, and estimation of hydrocarbon volume. The result of core analysis presents in target intervals are consist of seven sandstone litofacies which are Slvf, Ssf, Ssvf, Smf, Sfmf, Spcvf, and Swvf, and also one claystone litofacies which are Cm. Based on biostratigraphy analysis, core analysis, and electrofacies interpretation, the research area depositional environment of research area is shallow marine from inner neritic to middle neritic (0 - 100 m) in the age of Middle Miocene with facies association consists of upper shoreface, lower shoreface, and offshore. The distribution of petrophysical properties of volume of shale, porosity, and water saturation is qualitatively controlled by the distribution of facies and the direction of deposition from the Northwest to the Southeast. The results of volumetric estimation show the volume from the reservoir interval of Tawun Formation of layer V equal to 1,679 MMSTB and layer VIII equal to 0,652 MMSTB. The total hydrocarbon volumetric estimation on Sukorejo field is 2,331 MMSTB.